Sistem Aplikasi Pengadaan Barang Dan Jasa Dengan Menggunakan Javascript, Mysql Dan Internet - Marliana Sari (Sekolah Tinggi Teknik - PLN, 2016)
Already we can not deny anymore that the development of the Internet has a lot of petrified human work activity be it in education, politics, and economy, especially business. The active role of the internet is very active as a means of effective and efficient in running the business, especially in the provision of goods and services. The supply of goods and services used to be done manually every vendor that came Client then ask the client procurement what is required by the client. But with the internet can change the behavior of these business processes that previously this process takes a long time and mamakan enough money. With the Internet is the business process can provide ease of administration for both the buyers and partners as the vendor / supplier. The application system is connected to the Internet to make the process of purchasing administration can be done anytime and anywhere.The main advantage transactions of goods and services providers to the Internet include saving money, time, and the extra work load that is normally associated with the write-menulis.Keuntungan work is also not just bigger to saving money alone but also simplifies the whole process. Optimal plans that can be communicated quickly to the suppliers, and therefore can reduce the cost and waste that is usually found in the supply chain.